E-group art journal therapy to reduce adolescents’ levels of stress, anxiety, and depression - Widiasavitri, Putu Nugrahaeni; Dwijayani, Ni Komang Karmini; Gagahriyanto, Muhammad Anjar; Haryati, Tuningsih (Universitas Mercu Buana Yogyakarta, 2024)
Depression, anxiety, and stress in adolescents require therapy as these conditions are likely to cause harm to both the individuals experiencing them and their surroundings. Therefore, it is important to create an intervention for this age group. E-Group Art Journal Therapy is an intervention which involves art as its approach and is conducted in groups through an online platform, Zoom Meeting. In this study, ten participants were divided into two groups: the control group and the experimental group. Participants were recruited through non-random sampling using these criteria: they were required to be active students, reside in Bali, be between 18-23 years old, have a moderate level of stress, moderate level of anxiety, low level of depression based on Depression Anxiety Stress Scale (DASS), and agree to participate in the study. This study employed a mixed method which produced both quantitative and qualitative data that were analyzed with Wilcoxon rank-sum test and theoretical coding. The results showed that there were score differences between the control group and the experimental group in terms of depression, anxiety, and stress levels. Qualitatively, there were also psychological changes among the five participants from the experimental group. Implementing an intervention in groups could be beneficial because the group activities created mutual situations. Creating artwork also contributed to therapeutic processes. Quantitatively, there was a significant decrease in depression score. Qualitatively, E-GAJT encouraged the participants to believe in their potential despite their upbringing in an unsupportive environment. This encouragement fostered greater courage, enabling them to take steps toward achieving goals and creating healthier boundaries. Keyword: Adolescent, DASS; group; psychotherapy; virtual.